IMPLEMENTASI STRATEGI DIGITAL MARKETING GUNA MENARIK MINAT NASABAH PEMULA PADA PT PEGADAIAN (PERSERO) CABANG JIMBARAN - SORMIN, ANGGUN KARUNIA; WIJAYATI, NI LUH MADE; SANTRA, I KETUT (GANEC SWARA, 2024)
With the rapid development of the times in this digital era, it certainly helps entrepreneurs to market their product widely. This study aims to determine the implementation of what digital marketing strategies are implemented and what digital marketing strategies are used to attract new customer at PT Pegadaian (Persero) Jimbaran Branch. This research uses qualitative methods and descriptive research types. Data collection techniques using observation, interviews and documentation. Data collection techniques using observation, interviews and documentation. Based on the results of research and analysis, it can be concluded that first, the implementation of digital marketing strategies at PT Pegadaian (Persero) Jombaran uses a promotion mix, namely a combination of marketing between conventional digital marketing and digital implementation, namely implementing 5D (Digital Devices, Digital Platfroms, Digital Media, Digital Data, and Digital Technology). Second, the digital marketing strategy to attract new customers used by PT Pegadaian (Persero) Jimbaran branch is Pegadaian Digital Service. As for the output of the results of this study, namely a tiktok account containing content, a flowchart to make it easier to create content, and a barcode that is used as a means of employee evaluation material, the barcode contains suggestions or comments from customers.